2010
DOI: 10.1002/jrs.2823
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐enhanced Raman spectra of dimethoate and omethoate

Abstract: Surface-enhanced Raman scattering (SERS) spectra are presented and analyzed for two important organophosphate pesticides, dimethoate (DMT) and omethoate (OMT). Very detailed SERS spectra were obtained by aggregated Ag hydrosols, both in aqueous suspension and dried on a glass substrate. The SERS and ordinary Raman spectra of DMT do not resemble each other, suggesting that a chemical reaction immediately occurs when DMT is adsorbed onto the metal surface. We propose that the reaction product is OMT, which is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…2(a) is the SERS signal of the omethoate pesticide, and the enhancement effect of the gold nanoparticles is obvious. Among the peaks, the obvious Raman peaks at 394, 413, 564 and 770 cm À1 are consistent with the research results of Guerrini et al 22 We also get the Raman characteristic of chlorpyrifos (346, 634, 677 cm À1 ), and can be regarded as the focus area of this study. In this experiment, therefore, direct measurement of the areas containing pesticide residues on the apple surface did not produce detectable Raman spectra of omethoate and chlorpyrifos.…”
Section: Resultssupporting
confidence: 74%
“…2(a) is the SERS signal of the omethoate pesticide, and the enhancement effect of the gold nanoparticles is obvious. Among the peaks, the obvious Raman peaks at 394, 413, 564 and 770 cm À1 are consistent with the research results of Guerrini et al 22 We also get the Raman characteristic of chlorpyrifos (346, 634, 677 cm À1 ), and can be regarded as the focus area of this study. In this experiment, therefore, direct measurement of the areas containing pesticide residues on the apple surface did not produce detectable Raman spectra of omethoate and chlorpyrifos.…”
Section: Resultssupporting
confidence: 74%
“…Therefore, there are many SERS studies of food analysis that are based on these substrates, especially favored by researchers in the chemistry/engineering areas (including food science) because of lack of capacity to fabricate sophisticated substrates. The use of Au and Ag colloids has been demonstrated in the detection of food additives, notably sodium benzoate, β‐hydroxy‐β‐methylbutanoic acid (HMB), L‐carnitine, N‐methylglycocyamine (Podstawka and others ), monosodium glutamate (Peica and others ), butylated hydroxyanisole (Yao and others ), Ponceau 4R (Xie and others ) and the chemical contaminants tricyclazole (Tang and others ), methamidophos (Xie and others ), omethoate, dimethoate (Guerrini and others ), nitrofurans (Xie and others ), melamine (Zhang and others ). The LOD varied from 2 ppb to 10 ppm, mainly depending on the composition and size of the colloids, chemical structure of analytes, and sample preparation and analysis procedures.…”
Section: Sers Substrate Development For the Chemical Analysis Of Foodmentioning
confidence: 99%
“…Recent development of SERS methods for pesticide detection progressed from detection in simple solvents to complex food matrices. The detection of pesticides in simple solvents was mainly from the study that intended to demonstrate the potential application of SERS substrates and SERS methods (Wang and others ; Guerrini and others ; Yuan and others ; Liu and others ; Xie and others ; Yu and White ) .…”
Section: Applications Of Sers In the Chemical Analysis Of Foodmentioning
confidence: 99%
“…SERS has been used for trace analyses and detection of residue of different organophosphorous pesticides and insecticides by employing various NSs, such as a solution of 100 nm Ag nanocubes or a Klarite Au‐coated SERS‐active substrate . For instance, Liu et al reported a detection of dimethoate at concentrations of 0.5 to 10 μg ml −1 acquired by confocal Raman microspectrometry with Klarite substrate.…”
Section: Introductionmentioning
confidence: 99%